2003
DOI: 10.2307/30040613
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Agency Consequences of Ownership Dispersion Among the Directors of Private Family Firms.

Abstract: Using an agency-theoretic lens and insights drawn from the behavioral economics and family business literatures, we developed hypotheses concerning the effect of dispersion of ownership on the use of debt by private family-owned and family-managed firms. A field study of 1,464 family firms was conducted. Results suggest that, during periods of market growth, the relationship between the use of debt and the dispersion of ownership among directors at family firms can be graphed as a U-shaped curve. The principal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
681
3
29

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 705 publications
(741 citation statements)
references
References 58 publications
(37 reference statements)
27
681
3
29
Order By: Relevance
“…Instead, when family owners are not involved in management, they may prefer to increase debt to reduce manager's opportunistic behaviors (Stulz, 1988). However, recent research has shown that family involvement in the business many lead to other kinds of agency problem Chrisman et al, 2004;Schulze et al, 2001Schulze et al, , 2003aSchulze et al, , 2003bVillalonga & Amit, 2006) engendered by self-control and altruism (Lubatkin et al, 2005). In addition, Blanco-Mazagatos et al, (2007) shows that family involvement across generations may determine agency conflicts which may influence family firm's capital structure choices.…”
Section: Theoretical Framework For Family Firms' Capital Structurementioning
confidence: 99%
“…Instead, when family owners are not involved in management, they may prefer to increase debt to reduce manager's opportunistic behaviors (Stulz, 1988). However, recent research has shown that family involvement in the business many lead to other kinds of agency problem Chrisman et al, 2004;Schulze et al, 2001Schulze et al, , 2003aSchulze et al, , 2003bVillalonga & Amit, 2006) engendered by self-control and altruism (Lubatkin et al, 2005). In addition, Blanco-Mazagatos et al, (2007) shows that family involvement across generations may determine agency conflicts which may influence family firm's capital structure choices.…”
Section: Theoretical Framework For Family Firms' Capital Structurementioning
confidence: 99%
“…Furthermore, all of the choices concerning the governance structure seem to diverge from prescriptions and suggestions expressed by the mainstream theory (Schwartz & Barnes, 1991;Schulze et al, 2003). Although literature emphasizes the role of non-family members in seizing environmental opportunities, developing a better awareness of the company's challenges, and, ultimately, in fostering innovation, our analysis suggests that the different approaches to innovation are not the result of any specific choice as regards the presence of non-family members in the Board.…”
Section: Discussionmentioning
confidence: 78%
“…Outsiders can promote a better awareness of managerial issues, they can provide alternative information, experience, perspectives, and they can develop a greater ability to interpret changes in the environment (Schulze, Lubatkin, & Dino, 2003;Bammens, Voordeckers &Van Gils, 2011). Moreover, they can contribute to resolving internal conflicts and to achieving consensus within the BoD (Bammens et al, 2011).…”
Section: Governance Assets In Family Smesmentioning
confidence: 99%
See 1 more Smart Citation
“…In attempts to understand this rapport, scholars have drawn on a range of theories such as agency theory (Schulze, Lubatkin, Dino, & Buchholtz, 2001;Schulze, Lubatkin, & Dino, 2003), stewardship theory (Miller, Breton-Miller, & Scholnick, 2008) and the resource-based view of the firm (Habbershon & Williams, 1999;Sirmon & Hitt, 2003) and each has revealed evidence of both benefits and costs of family involvement.…”
Section: Literature Reviewmentioning
confidence: 99%